Gambaran Dukungan Keluarga, Waktu Penanganan, dan Tingkat Keparahan Pasien Pasca-Stroke: Profile of Family Support, Onset-to-Treatment Time, and Stroke Severity among Post-Stroke Patients - Kevin Ramadhan Pratama; Suyanto Suyanto; Mohammad Arifin Noor (Universitas Ngudi Waluyo, 2026)
Family support plays an important role in assisting post-stroke patients during the care and recovery process, while the timeliness of stroke treatment is a crucial factor influencing patients’ clinical conditions. This study aimed to describe family support, stroke treatment time, and the severity of post-stroke patients at Sultan Agung Islamic Hospital, Semarang. This study employed a descriptive design with a cross-sectional approach. A total of 110 post-stroke patients were selected using a purposive sampling technique. The research instruments included a family support questionnaire, a stroke treatment time questionnaire, and the National Institutes of Health Stroke Scale (NIHSS) to assess stroke severity. Data were analyzed descriptively using frequency and percentage distributions. The results showed that most post-stroke patients received moderate family support (79.1%), onset-to-treatment time was predominantly categorized as moderately delayed (79.1%), and the stroke severity was mostly classified as severe neurological deficit (45.5%). This study implies the importance of strengthening pre-hospital management education for families to accelerate response time in stroke treatment.